Decreased Self-Esteem and Depression Experienced by Elderly People with Stroke - Gardha Rias Arsy; Sri Hindriyastuti; Wafda Nailil Muna (Poltekkes Kemenkes Aceh, 2025)
Background: Neurological dysfunction, which leads to stroke, is the third leading cause of disability worldwide. Stroke-related conditions, such as paralysis of the extremities, are particularly stressful for the elderly. Feelings of helplessness, depression, and low self-esteem are common. This is because they feel like a burden on their families and are ashamed to burden their children. Purpose: Exploring the experience of depression and low self-esteem in older adults who have experienced stroke. Methods: This study used a qualitative method with a phenomenological approach. Seven elderly stroke patients experiencing psychosocial problems and requiring full family support were participants. The sample size was determined using purposive sampling. Participants were selected based on inclusion criteria, including being diagnosed with stroke for more than three years, being able to communicate, and experiencing psychosocial problems. The research used Interpretative Phenomenology Analysis (IPA) as the data analysis technique. Results: Based on the research results, 3 themes were obtained, namely 1. Feeling like a burden on the family (Living with stroke was felt by participants as a burden for the family), Theme 2: Feeling limited in doing something (All participants considered themselves unable to do physical activities freely) and Theme 3: Experiencing low self-esteem. (The elderly with stroke felt that they were no longer productive, could only depend on their families and experienced feelings of helplessness and worthlessness). Conclusion: Elderly stroke survivors tend to experience psychological disorders characterized by depression, such as sadness, anger, disappointment, feelings of helplessness, and feeling like a burden on their families. Furthermore, socially, they also tend to have low self-esteem, as evidenced by feelings of being restricted and incapable of engaging in social activities.